Networking of accountants and the use of strategic management accounting techniques in hospitals: the moderating role of hospital information systems and organizational culture (Study of Kerman hospitals) - Amir Fazel; Behnam Karamshahi; Azin Harandi (Tehran University of Medical Sciences, 2023)
Background and Purpose: Today, the use of strategic management accounting techniques within organizations is expanding rapidly. However, the implementation of these techniques and the examination of variables affecting them in hospitals remain largely unexplored. The aim of this research is to investigate the impact of accountants' networking on the use of strategic management accounting techniques, considering the moderating roles of hospital information systems and organizational culture. Methods: This descriptive-correlational study utilized a 43-question questionnaire, whose validity and reliability were confirmed. The statistical population consisted of all employees and accountants in the finance and accounting departments of hospitals in Kerman, totaling 141 individuals. The census method was used to complete the questionnaire, with 139 questionnaires returned. Structural equation modeling and Smart PLS 3 software were used to test the research model. Results: Statistical indices confirmed the model's appropriate fit (GOF=0.738). Networking of accountants, hospital information systems, and results-oriented culture positively influence the use of strategic management accounting techniques, whereas innovative culture has no effect. Additionally, hospital information systems and results-oriented culture positively moderate the relationship between accountants' networking and the implementation of strategic management accounting techniques, while innovative culture does not have any moderating effect. Conclusion: This research contributes to the expansion of strategic management accounting techniques in hospitals and highlights the importance of influencing factors. Hospitals should apply these techniques while giving due consideration to the factors that affect them.